COVID-19 and changes in college student educational expectations and health by disability status - Andrew Halpern-Manners; Jane D. McLeod; Elizabeth M. Anderson; Emily A. Ekl (Elsevier, 2022)
This study examines the implications of the coronavirus pandemic for college students' health and education, with special attention to variation by disability status. Disaster research supports the hypothesis that students with disabilities will experience higher-than-usual levels of pandemic-related stress, which could lead to re-evaluations of their educational expectations and declines in health. We evaluate this hypothesis by modeling changes in students' (1) mental and physical health and (2) educational expectations during the first year (spring of 2020 to spring of 2021) of the pandemic, using survey data collected from a population-based sample of college students in the state of Indiana. Although we observe across-the-board declines in both domains, students with disabilities were especially vulnerable. Mediation analyses suggest that differential exposure to financial and illness-related stressors is partially to blame, explaining a significant portion of the group differences between students with and without disabilities. We interpret these results as evidence of the unique vulnerabilities associated with disability status and its wide-ranging importance as a dimension of social stratification.